Tinjauan Ketidakpuasan Pasien Lama Terhadap Pelayanan Pendaftaran Rawat Jalan Di Rumah Sakit Menteng Mitra Afia - Nur Endah Sari; Gama Bagus Kuntoadi (MEDICORDHIF Jurnal Rekam Medis, 2018)
ABSTRACT The hospital is one of the health service facilities chosen by the community in obtaining health services. Registration is the initial gate of a hospital service, this is where the important role of the registration officer, must be able to give a comfortable impression so that patients can feel the satisfaction of hospital services. Patient satisfaction consists of 5 dimensions namely tangible, responsiveness, reliability, assurance, and empathy. This research was conducted based on 5 dimensions of service quality, which was felt by old patients towards outpatient registration officers, namely the statement "satisfied" there was empathy dimension of 83.2%, the statement "dissatisfied" in the tangible dimension of 7.4%, and the statement "neutral" on the dimensions of reliability that is equal to 9.4%. Suggestion to the old patient outpatient registration officer is to conduct periodic refresher program on "excellent service" namely tangible, reliability, responsiveness, assurance, and empathy in entering the hospital program, especially the review of waiting room facilities in outpatient registration Keywords :medical record, satisfaction, dissatisfaction, service quality dimension